Valor nutricional do feno de Brachiaria decumbens em três idades - Matheus Anchieta Ramirez (2011)
Brachiaria decumbens forage is one well adapted to climate and soil conditions in Brazil, but focuses much of its dry matter production at certain times of year. The making hay of this plant enables supplementation of livestock during seasonal scarcity of fodder. The objective was to evaluate the nutritive value of Brachiaria decumbens hay cut at ages 56, 84 and 112 days of growth through indirect calorimetry tests using sheep (experiment I), techniques of in situ incubation (experiment II) and technical automátrica semi-in vitro gas production(experimentoIII). In the first experiment aimed to evaluate the contents of metabolizable energy (ME) and net energy (NE) of Brachiaria decumbens hay. We used 18 sheep distributed in a completely randomized design with three treatments and six replications, with treatments Haysobtained at 56, 84 and 112 days. For the measurement of gas exchange animals were housed in open-flow respirometric chamber for 24 hours. The contents of MS were similar (p> 0.05) being 2.1, 2.0, 1.7 kcal / kg DM, respectively for the plants with hay obtained at ages 56, 84 and 112days. The levels of EL, in kcal / kg were 1.3, 1.5 and 1.3, respectively, for hay at 56, 84 and 112 days. The total consumption of EL per unit of metabolic size (UTM) were similar among treatments, with values of 87.3, 91.0 and 76.1 kcal / UTM / day for hay at 56, 84 and 112 days respectively. IN total consumption per unit of metabolic size was lower for hay obtained at 112 days, 97.2 kcal / UTM (p <0.05) compared with those produced at 56 and 84 days, 135.0 and 119 , 7 kcal / UTM, respectively, which were similar (p> 0.05). In the second experiment evaluated the Brachiaria decumbens hay by in situ incubation technique. The experimentaldesign was a randomized block with split plot, where they were tested in three hay in the rumen fistulated heifers five blocks, seven incubation time. The incubation time were assessed at 0, 3, 6, 12, 24, 48 and 96 hours. The disappearance of dry matter, organic matter, crude protein, NDF and ADF were higher (p <0.05) for hay made from the plant at 56 days, 76.0%, 75.3%, 81.5%, 75.7%, 73.0% respectively, compared to hay made from plants at 84 days, 66.4%, 65.4%, 67.7%, 66.5%, 65.6%, respectively, and 112 days, 65.4%, 64.4%, 62.7%, 65.3%, 65.9%,respectively, which were similar (p> 0.05). Thus, we obtained a greater ruminal degradation of hay for 56 days. In experiment III the hay were evaluated by the technique of in vitro gas production. The statistical design adopted was randomized blocks with split-plot, and the threecut (56, 84 and 112 days) the plots, the ruminal inoculum blocks, and the reading times of gas production sub -plots. The highest yields of gases accumulated hay were obtained by the plant with 56 and 84 days, 183.9 and 177.1 mL / g DM. The age of 56 days had a higher total gas production. The results of these experiments indicate that the hay obtained with Brachiaria decumbens has 56 days to the nutritional value than those obtained with this plant at 84 and 112 days.